Rules with Discretion and Local Information* - Bowen, T. Renee; Kreps, David M.; Skrzypacz, Andrzej (Quarterly Journal of Economics, 2013)
Abstract To ensure that individual actors take certain actions, community enforcement may be required. This can present a rules-versus-discretion dilemma: it can become impossible to employ discretion based on information that is not widely held, because the wider community is unable to verify how the information was used. Instead, actions may need to conform to simple and widely verifiable rules. We study when discretion in the form of exceptions to a simple rule can be implemented, if the information is shared by the action taker and a second party, who is able to verify for the larger group that an exception is warranted. In particular, we compare protocols where the second party excuses the action taker from taking the action ex ante with protocols where the second party instead forgives a rule-breaking actor ex post.